Screening for various non communicable diseases: a community based multi-diagnostic mega camp approach study from Raichur, Karnataka - S., Amruth Reddy; Reddy A., Sai Anurag; Takalkar, Anant A. (International Journal of Advances in Medicine, 2021)
Background: The 77% of all non-communicable illnesses (NCDs) deaths are in low-and middle-income countries. Cardiovascular diseases account for most NCD deaths, or 17.9 million people annually, followed by cancers (9.3 million), respiratory diseases (4.1 million), and diabetes (1.5 million). These 4 groups of diseases account for over 80% of all premature NCD deaths. Objective was to study prevalence of NCDs and its trends with respect to age and gender. Methods: The present community based descriptive observational study was conducted at Navodaya medical college hospital and research centre, Raichur that caters Urban and rural area of Raichur. The 4063 apparently healthy population from urban and rural part of Raichur were screened during the multi diagnostic mega camp at urban and rural areas around Raichur during the period of January to September 2021. Results: Prevalence of diabetes in our study was 46.3%, hypertension 45.3%, cataract 46.3% and COPD as 20.7%. Prevalence of diabetes was more in 41-60 years i.e., 41.6%. Prevalence of hypertension was more in 41-50 years i.e., 25.3%. Prevalence of diabetes was more in males i.e., 54.1%. Prevalence of hypertension was more in males i.e., 50.8%. Conclusions: Prevalence of all NCDs was more in above 40 years and more in males except COPD.